Label-Free Quantitative Proteome Analysis Reveals the Underlying Mechanisms of Grain Nuclear Proteins Involved in Wheat Water-Deficit Response - Li, Tingting; Zhu, Dong; Han, Zhisheng; Zhang, Junwei; Zhang, Ming; Yan, Yueming (Frontiers in Plant Science, 2021)
In this study, we performed the first nuclear proteome analysis of wheat developing grains under water deficit by using a label-free based quantitative proteomic approach. In total, we identified 625 unique proteins as differentially accumulated proteins (DAPs), of which 398 DAPs were predicted to be localized in nucleus. Under water deficit, 146 DAPs were upregulated and mainly involved in the stress response and oxidation-reduction process, while 252 were downregulated and mainly participated in translation, the cellular amino metabolic process, and the oxidation-reduction process. The cis-acting elements analysis of the key nuclear DAPs encoding genes demonstrated that most of these genes contained the same cis-acting elements in the promoter region, mainly including ABRE involved in abscisic acid response, antioxidant response element ARE, MYB responsive to drought regulation and MYC responsive to early drought. The cis-acting elements related to environmental stress and hormones response were relatively abundant. The transcription expression profiling of the nuclear upregulated DAPs encoding genes under different organs, developmental stages and abiotic stresses was further detected by RNA-seq and qRT-PCR, and more than 50% of these genes showed consistency between transcription and translation expression. Finally, we proposed a putative synergistic responsive network of wheat nuclear proteome to water deficit, revealing the underlying mechanisms of wheat grain nuclear proteome in response to water deficit.